Exploring Lifestyle and Literacy Effects on Millennials’ Saving in Islamic Banks - Amaliah, Ima; Anjani, Selsa Putri; Aspiranti, Tasya; Nurhayati, Nunung (Journal of Social Science and Business Studies, 2025)
This research examines the saving intentions of millennials in Bandung City toward Islamic banking by applying a descriptive quantitative method. The study targets individuals aged 29–44 who have not yet opened an Islamic bank account and are distributed across 30 districts in Bandung. The main purpose is to analyze how lifestyle patterns, financial literacy, and demographic characteristics influence their willingness to save in Islamic banks. The analysis shows that female millennials between 24–28 years old express a stronger intention to save compared to other groups. Educational background, whether high school or university level, presents no significant differences in saving interest. By contrast, occupational status provides clearer distinctions: male civil servants and female employees in the private sector exhibit higher levels of intention. Income data reveal that most respondents earn between IDR 2–5 million monthly, placing them in the lower-middle income bracket. The findings also suggest that saving preferences are shaped more by individual information seeking rather than by family expectations or peer influence. Although their comprehension of Islamic financial principles is relatively limited reducing their level of trust, millennials demonstrate considerable digital literacy and confidence in using Islamic banking services. Overall, the study concludes that millennials make financial choices in a rational and independent manner but still require more accessible digital financial education. To capture this market, Islamic banks are advised to integrate Islamic values with digital literacy initiatives and foster closer engagement with millennial communities to build long-term trust and loyalty.